Vibration Analysis of Fused Deposition Modelling Printed Lattice Structure Bar for Application in Automated Device - S. Azmi, M; Ismail, R; Hasan, R; R. Alkahari, M (International Journal of Engineering and Technology, 2018)
The purpose of this study is to investigate the effect of size of strut radius to the natural frequencies of acrylonitrile-butadiene-styrene (ABS) polymer lattice-structure bar material by using vibration technique. The lattice structured cellular material parts with body-centered-cubic (BCC) topological design are manufactured using fused deposition modeling (FDM) additive manufacturing (AM) technique with aim to reduce the overall weight of automated device. The specimens are tested by using set up consist of fabricated test rig, accelerometer, force sensor, power amplifier, shaker and signal generator/analyzer. The first mode natural frequency obtained from the vibration testing for specimen with 1.0 mm strut radius is 278 Hz while specimen with 1.2 mm strut radius is 441 Hz. The results obtained from vibration testing show that bigger size of strut radius will yield higher natural frequencies and the lattice structure bar is suitable for use as arm body part in automated device. By utilizing FDM AM, industry will be able to benefit in term of saving in fabrication cost as well as energy consumption.Â